Serial MR Imaging Findings of Acute Hemorrhagic Leukoencephalitis: A Case Report - Lee, Ho Yun; Chang, Kee-Hyun; Kim, Ji Hoon; Na, Dong Gyu; Kwon, Bae Ju; Lee, Kwang-Woo; Park, Sung Hye (American Journal of Neuroradiology, 2005)
Summary: We report a patient with acute hemorrhagic leukoencephalitis with a focus on serial MR imaging findings. Initial MR imaging of a 42-year-old woman revealed a 2.5-cm focal nonhemorrhagic lesion in the left thalamus and internal capsule. Twenty-four days later, fever and altered consciousness developed, and MR imaging showed huge masslike lesions in both frontal lobes, mainly involving the white matter and the genu of the corpus callosum, with massive edematous swelling that contained multifocal small hemorrhages. Most lesions showed high apparent diffusion coefficient value with peripheral small areas of low apparent diffusion coefficient. On follow-up MR imaging obtained 49 days after initial MR imaging, the lesions progressed with increase in extent and development of rim-enhancing necrosis, despite steroid therapy. Following stereotactic biopsy and subsequent high-dose steroid treatment, the patient recovered with some neurologic sequelae. MR imaging obtained at 72 and 126 days revealed residual necrosis and cerebromalacia in the both frontal lobes.